A meta-analysis of mismatch negativity in children with attention deficit-hyperactivity disorders. (26th January 2016) - Cheng, Chia-Hsiung; Chan, Pei-Ying S.; Hsieh, Yu-Wei; Chen, Kuan-Fu
Highlights: MMN is an electrophysiological signal to assess automatic change-detection function. It remains ambiguous whether ADHD children show abnormal MMN responses. We performed a meta-analysis of MMN studies to examine the mean effect size. ADHD children showed reduced MMN amplitudes compared to healthy controls. These data suggest a decline of central auditory processing in children with ADHD. Abstract: Mismatch negativity (MMN) is an optimal neurophysiological signal to assess the integrity of auditory sensory memory and involuntary attention switch. The generation of MMN is independent of overt behavioral requirements, concentration or motivation, and thus serves as a suitable tool to study the perceptual function in children with attention deficit-hyperactivity disorders (ADHD). It remains unclear whether ADHD children showed altered MMN responses. Therefore we performed a meta-analysis of peer-reviewed MMN studies that had targeted both typically developed and ADHD children to examine the pooled effect size. The published articles between 1990 and 2014 were searched in PubMed, Medline, Cochrane, and CINAHL. The mean effect size and a 95% confidence interval (CI) were estimated. Six studies, consisting of 10 individual investigations, were included in the final analysis. A significant effect size of 0.28 was found ( p  = 0.028, 95% CI at 0.03–0.53). These results were also free from publication bias or heterogeneity. In conclusion, our meta-analysis results suggest ADHD children demonstrated a reduced MMN amplitude compared to healthy controls.